2022
DOI: 10.1111/apha.13888
|View full text |Cite
|
Sign up to set email alerts
|

Uremic toxins in chronic kidney disease highlight a fundamental gap in understanding their detrimental effects on cardiac electrophysiology and arrhythmogenesis

Abstract: Chronic kidney disease (CKD) and cardiovascular disease (CVD) have an estimated 700–800 and 523 million cases worldwide, respectively, with CVD being the leading cause of death in CKD patients. The pathophysiological interplay between the heart and kidneys is defined as the cardiorenal syndrome (CRS), in which worsening of kidney function is represented by increased plasma concentrations of uremic toxins (UTs), culminating in dialysis patients. As there is a high incidence of CVD in CKD patients, accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 122 publications
0
11
0
Order By: Relevance
“…Previously, exposure to IS and another UT, p-cresyl sulfate, has been shown to decrease repolarization currents in H9c2 rat ventricular cardiomyocytes and computer simulations [ 22 , 23 ]. Additional studies, including in vivo studies, have shown pro-arrhythmic consequences but failed to delve into potential mechanisms of action [ 13 ]. With this current study, we have shown that UTs can additionally influence ion channel functionality, resulting in electrophysiological disturbances that might lead to increased susceptibility to arrhythmias in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, exposure to IS and another UT, p-cresyl sulfate, has been shown to decrease repolarization currents in H9c2 rat ventricular cardiomyocytes and computer simulations [ 22 , 23 ]. Additional studies, including in vivo studies, have shown pro-arrhythmic consequences but failed to delve into potential mechanisms of action [ 13 ]. With this current study, we have shown that UTs can additionally influence ion channel functionality, resulting in electrophysiological disturbances that might lead to increased susceptibility to arrhythmias in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…All stock solutions were filtered and stored at −20 °C. Clinically relevant total UT concentrations were identified previously [ 13 ] and applied in all experiments. Albumin was present in all culture media to establish clinically relevant, free fraction concentrations of all UTs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the main causes of human death, cardiovascular diseases (CVD) occupy first place 1 . In addition, deaths from diabetes mellitus (DM) 2 and chronic kidney disease (CKD) 3 are mainly because of CVD. In patients with diabetes, glycaemic control has a significant effect in preventing the development and progression of microvascular or CV complications 4–7 .…”
Section: Introductionmentioning
confidence: 99%